2017
DOI: 10.1371/journal.pgen.1006761
|View full text |Cite
|
Sign up to set email alerts
|

Identification of breast cancer associated variants that modulate transcription factor binding

Abstract: Genome-wide association studies (GWAS) have discovered thousands loci associated with disease risk and quantitative traits, yet most of the variants responsible for risk remain uncharacterized. The majority of GWAS-identified loci are enriched for non-coding single-nucleotide polymorphisms (SNPs) and defining the molecular mechanism of risk is challenging. Many non-coding causal SNPs are hypothesized to alter transcription factor (TF) binding sites as the mechanism by which they affect organismal phenotypes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 76 publications
3
39
0
Order By: Relevance
“…The SNP resulted in a significant allelic imbalance between alleles C and T, nearly 79% and 21%, respectively in a set of MC7 cell lines ( Supplementary Figure 5 and Supplementary Table 13). Our findings corresponded to the results for rs8103622 in (36). Moreover, we checked the presence of DHSs and CTCF signals for the remaining tissue types: blood, liver and myeloid.…”
Section: Enrichment Of Genetic Variantssupporting
confidence: 87%
“…The SNP resulted in a significant allelic imbalance between alleles C and T, nearly 79% and 21%, respectively in a set of MC7 cell lines ( Supplementary Figure 5 and Supplementary Table 13). Our findings corresponded to the results for rs8103622 in (36). Moreover, we checked the presence of DHSs and CTCF signals for the remaining tissue types: blood, liver and myeloid.…”
Section: Enrichment Of Genetic Variantssupporting
confidence: 87%
“…Our method differs from existing single-locus GWAS methods 11,12,103 in that it enables stronger statements about causality and mechanism. Regarding causality, this is because a consistent genome-wide directional effect of SNPs predicted to affect TF binding due to sequence change (across a large set of TF binding sites; see Table 1a) is less susceptible to pleiotropy, LD, and allelic heterogeneity 103,105 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are instances in which experimental data allow us not only to identify SNPs that affect a biological process, but also to predict which SNP alleles promote the process and which SNP alleles hinder it, thereby enabling us to assess whether there is a systematic association between SNP alleles' direction of effect on the process and their direction of effect on a trait. Transcription factor (TF) binding, which plays a major role in human disease 1,[8][9][10][11][12] , represents an important case in which such signed functional annotations are available: because TFs have a tendency to bind to specific DNA sequences, it is possible to estimate whether the sequence change introduced by a SNP allele will increase or decrease binding of a TF 1,[13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Although we found no specific enrichment for variants in CTCF elements, numerous were within CTCF peaks. Recent evidence has shown that disruption of CTCF binding by common variants plays a role in determining the severity of influenza and breast cancer 64,65 , thus it likely represents a less common, yet important molecular mechanism. Additionally, modelling of rs10758656 showed near complete loss of open chromatin.…”
Section: Discussionmentioning
confidence: 99%